Centrifuge modelling of complex infrastructure-seabed interaction in the touchdown zone using fibre optic sensing - Zhechen, Hou; Fauzan, Sahdi; Colm, O'Beirne; Fraser, Bransby; Christophe, Gaudin; Phillip, Watson (2025)
A key challenge when designing risers and cables is to quantify the level of fatigue in the seabed touchdown zone, where cable/riser overbending and complex soil-structure-fluid interaction occur. In this study, soil-structure interaction was investigated in a geotechnical centrifuge using three-dimensional actuation to model the behaviour of a riser section instrumented with state-of-the-art fibre-optic sensors. Reconstituted natural carbonate silty sand was used to model the seabed. The acquisition of high-resolution data enables interpretation of the distribution of stress and contact force along the model riser under actively controlled (and realistic) heave, surge, and sway motions; as well as quantifying the resulting pitch and yaw rotations. The findings not only contribute to formulating new design approaches for risers used in the conventional energy sector, but also advance understanding relevant to the burgeoning offshore renewables sector by informing dynamic power cable design.